Brand Reputation Management in a Chinese Higher Educational Institution - Xia, Xiaofang (Pacific International Journal, 2024)
Brand reputation management is of increasing importance in the highly competitive landscape of higher education institutions, particularly in the context of Chinese culture. This study explores the challenges and strategies related to managing brand reputation in a Chinese higher educational institution. It highlights the significance of brand reputation in attracting students, faculty, and external support, making it a critical aspect for these institutions. Drawing on the Reputation Quotient Model, this research examines reputation in terms of innovation, workplace culture, social responsibility, financial performance, emotional appeal, and products and services. It also explores the interplay between brand association, brand identity, and the overall quality of academic services and how these factors affect the perception of the institution. The study's findings reveal that the perceived quality, brand association, and brand identity play pivotal roles in shaping the brand reputation management of Chinese higher education institutions. The research provides valuable insights for institutions to enhance their brand management strategies, thus attracting and retaining high-quality faculty and students while fostering engagement with stakeholders and alumni. Additionally, it emphasizes the need for institutions to balance global and local perspectives to maintain brand relevance and reputation in the competitive higher education market. Ultimately, the study underscores the critical role brand reputation plays in the success of higher education institutions in China.